Extreme Risk-Taking Behaviors in Patients With Eating Disorders - Stein, Daniel; Keller, Shikma; Ifergan, Inbar Sharav; Shilton, Tal; Toledano, Anat; Pelleg, Maya Treves; Witztum, Eliezer (Frontiers in Psychiatry, 2020)
Background Patients with eating disorders (EDs) engage in different self-inflicted at-risk behaviors, including suicide, attempted suicide and non-suicidal self-injury. Our aim was to describe the occurrence and underlying motivations of non-suicidal extreme risk-taking behaviors in patients with EDs. Methods Four cases from different treatment centers in Israel were analyzed. Results All patients were females hospitalized in inpatient settings because of long lasting anorexia nervosa (AN) with either binge/purge or purging episodes (AN-B/P/AN-P), including in most cases both self-induced voting and laxative abuse. Case (1) was an adolescent also diagnosed with type 1 diabetes mellitus. She abused insulin, both omission and overdose, was highly suicidal, and suffered from comorbid oppositional behavior, depression and anxiety. Case (2) was a 24-years old woman, transitioning from restricting to AN with vomiting and laxative use during inpatient treatment. She was also diagnosed with attention deficit hyperactivity disorder, depression, anxiety, and suicidal thoughts. In hospital, she developed excessive water consumption, leading to very low urine concentrations and sodium levels, and one episode of loss of consciousness. Case (3) was in her late thirties, demonstrating particularly massive laxative abuse. She also suffered from alcohol addiction, sexual trauma, and one attempted suicide. During hospitalization she developed laxative-abuse-related rectal prolapse that was successfully operated. Nonetheless, after operation she resumed laxative abuse. Case (4) was a 23-year old pregnant women with highly active AN-B/P during pregnancy. She was hospitalized at 23 weeks of gestation following abdominal pressure. She only partly complied with inpatient treatment, discharged herself against medical advice after 5 weeks, and gave birth at week 34. Discussion: All cases were females with long-standing B/P type AN, often with multiple purging behaviors, other impulsive and non-impulsive comorbidities, and many environmental vulnerabilities. Different motivations were found for these extreme behaviors in addition to ED-related factors, mostly not related to suicide. The severity of the medical and psychological condition required multimodal medical and psychological inpatient interventions. The patients mostly did not comply with their treatment, showing considerable indifference to their grave medical condition.